Reinforcing potential of micro- and nano-sized fibers in the starch-based biocomposites - Nattakan Soykeabkaew (2018)
Starch-based biocomposites reinforced with jute (micro-sized fiber) and bacterial cellulose (BC) (nano-sized fiber) were prepared by film casting. Reinforcement in the composites is essentially influenced by fiber nature, and amount of loading. The optimum amount of fiber loading for jute and bacterial cellulose in each composite system are 60. wt% and 50. wt% (of starch weight), respectively. Mechanical properties are largely improved due to the strong hydrogen interaction between the starch matrix and cellulose fiber together with good fiber dispersion and impregnation in these composites revealed by SEM. The composites reinforced with 40. wt% or higher bacterial cellulose contents have markedly superior mechanical properties than those reinforced with jute. Young's modulus and tensile strength of the optimum 50. wt% bacterial cellulose reinforced composite averaged 2.6. GPa and 58. MPa, respectively. These values are 106-fold and 20-fold more than the pure starch/glycerol film. DMTA revealed that the presence of bacterial cellulose (with optimum loading) significantly enhanced the storage modulus and glass transition temperature of the composite, with a 35. °C increment. Thermal degradation of the bacterial cellulose component occurred at higher temperatures implying improved thermal stability. The composites reinforced with bacterial cellulose also had much better water resistance than those associated with jute. In addition, even at high fiber loading, the composites reinforced by bacterial cellulose clearly retain an exceptional level of optical transparency owing to the effect of the nano-sized fibers and also good interfacial bonding between the matrix and bacterial cellulose. © 2012 Elsevier Ltd.